NUMERICAL ANALYSIS OF Al2O3/WATER NANOFLUIDS NATURAL CONVECTION IN A WAVY WALLED CAVITY - Abu-Nada, Eiyad; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2011)
In the present work, heat transfer enhancement of Al2O3-water nanofluids in natural convection applied to differentially heated wavy cavities is investigated numerically. The governing equations are written in stream function-vorticity form and solved by using the finite volume technique. The effective thermal conductivity and viscosity of the nanofluid are approximated by the Maxwell-Garnetts and Brinkman models, respectively. The solutions are presented by streamlines, isotherms, local and mean Nusselt numbers, and velocity profiles for different Rayleigh numbers (10(3) <= Ra <= 10(5)), amplitude of wavy wall (0.85 <= a <= 1.1), and different volume fraction of nanofluids (phi = 0.05 and 0.1). It is observed that the addition of a nanoparticle of Al2O3 into the base fluid increases the mean Nusselt number. It is also more effective on flow field than that of temperature distribution. The geometry parameter or surface waviness can be decided to heat transfer regime even for the same Rayleigh number.
Keywords: Heat-Transfer Enhancement; Entropy Generation; Enclosure; Flows